1983
DOI: 10.3181/00379727-173-41695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vagotomy on Postcastration Gonadotropin Secretion in Male Rats

Abstract: The postcastration increase in gonadotropins was studied in intact and vagotomized male rats. Rats underwent vagotomy or sham surgery immediately prior to castration. In the first experiment, rats were bled before castration and at 1, 2, 4, and 7 days after castration. Serum LH and FSH were significantly lower in vagotomized rats 1 day after castration. On Days 2, 4, and 7 postcastration, serum gonadotropin levels were generally not different among experimental groups. In a second experiment, rats were decapit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Previous studies have also demonstrated that levels of high-and low-density lipoproteins were normal in abdominally vagotomized rats (Ojeda et al, 1983). Ovarian function is not altered in animals subjected to reduced food intake to mimic the body weight loss induced by vagotomy (Burden and Lawrence, 1977;Allen et al, 1983). Collectively, these observations suggest that altered ovarian functions subsequent to vagotomy are not nonspecific effects attributable to weight loss.…”
Section: Av-lulo (4)supporting
confidence: 48%
“…Previous studies have also demonstrated that levels of high-and low-density lipoproteins were normal in abdominally vagotomized rats (Ojeda et al, 1983). Ovarian function is not altered in animals subjected to reduced food intake to mimic the body weight loss induced by vagotomy (Burden and Lawrence, 1977;Allen et al, 1983). Collectively, these observations suggest that altered ovarian functions subsequent to vagotomy are not nonspecific effects attributable to weight loss.…”
Section: Av-lulo (4)supporting
confidence: 48%
“…Concerning the role of the vagus nerve, bilateral vagotomy has been reported to have a transient suppressive effect on bilateral orchidectomy‐induced gonadotropin response ( 68). In adult rats, unilateral (right‐sided) transection of the vagus nerve induces a significant luteinizing hormone rise ( 69) while, in peripubertal hemicastrated rats, right‐sided vagotomy combined with right‐sided hemiorchidectomy decreases serum gonadotropin concentrations and testosterone secretion ( 70).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic lateralization is, however, not restricted to females. Pronounced morphological differences in the central nervous system-testis axis of male rodents, and humans provide plausible hypotheses for lateralized function at the hypothalamic level [11][12][13][14]. In fact, gonadotropin-releasing hormone (GnRH) cells were found in higher numbers in the right side of the brain [15] that is consistent with the larger amount of the neurohormone produced in the right side, detectable however exclusively in the morning period [16].…”
Section: Introductionmentioning
confidence: 96%